MENYINGKAP MAKNA AMAN DALAM SYAIR “AL-MAR’U YAHSABU ANNAHU MAKMUN” KARANGAN HASYIM KAMALUDDIN AL-HILLI (ANALISIS PSIKOLOGI PENGARANG) - Mushfiroh, Dewi Maisyah; Mas’udah, Amaliyah Nur; Habibah, Alya Nur; Fauziyah, Adinda Rizeky; Shofiyah, Naurotus (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This study aims to uncover the meaning of security according to the human perspective in the poem entitled Almar'u yahsabu annahu makmun by Hasyim Kamaluddin Al-Hilli with the study of Author Psychology. The poem entitled Almar'u yahsabu annahu makmun is a poem that discusses the tragedy of the karbala war, namely the tragedy of the killing of sayyid Husain, the grandson of the Prophet Muhammad. This poem was created during the Uthmaniy reign by Hasyim Kamaluddin Al-Hilly. This research uses descriptive qualitative research in the form of library research using the study of author psychology. In this study, it has been found that the meaning of security according to the human perspective has been refuted by Hasyim Kamaluddiin in his poem Almar'u yahsabu annahu makmun in the first and second stanzas, in the fourth and fifth stanzas Hasyim also explains the message of life that must be considered by humans and by using the example of the Karbala war tragedy which killed the Prophet's grandson in a tragic way adds knowledge to the reader that the sense of security of danger in the world is a trick according to the second stanza.